DOES THE TYPE OF SET AND FINAL SCORE CHANGE TIME INDICATORS IN BEACH VOLLEYBALL? A STUDY DURING BRAZILIAN SCHOOL CHAMPIONSHIP - Yago Pessoa da Costa; Luiz Roberto Paiva-Junior; Edilberto Fernandes Pereira-Junior; Elizabeth Lourdes Soares da Silva; Antonio García-de-Alcaraz; Mauro Hernández; Gilmário Ricarte Batista (Journal of Physical Education)
ABSTRACT This study aimed to compare temporal indicators according to the type of set and final score difference. Twenty-five teams of male beach volleyball players (15 - 17 years old) competed in Brazilian School Championship, national stage. 21 matches, 42 sets, and 1374 rallies were observed. The variables analyzed were rally duration, rest time between rallies, total work time, total rest time, duration of the set, rest time : work time ratio, and the number of rallies. Time indicators were compared between the type of set (1st set Vs. 2nd set) and balance categories according to the difference in the final score (unbalanced, moderate balance, and balanced), using t-test and one-way ANOVA, respectively. No significant difference was found between the 1st and 2nd set, although a moderate effect was observed in total work time between sets. Moreover, the final score difference influences the duration of set, total work time, and total work-rest show a linear tendency between balanced levels. The temporal indicators do not seem to change concerning the type of set. However, there is a tendency for an increase in working time from the 1st to the 2nd set. Finally, the score influences the duration of the set, total work time, and total rest time, without modifying the effort : rest ratio.